(3GdQSGdI GdLGeYI ddCTjGA ef SQ GdNdjbI hUfYI GdWHjYIs - (3HdjfGS GdMcjes
(3ChdgG (B:s
(3Cbhd Ydi cJGHi gPG hCUa GdMceI GdJi CHJOCf HgG GSJeYhG MceJi dJfaP ai CagGece hJNU WHGFYce s
(3BNQgG (B:s
(3hdPdc SejJ gQeS GdeKdK HGdMceI GfJgi GdcJGH HMeO Gddg hYhfg s
(3GfXQ GdYdd GdLGeY ddCTjGAs
(3LejYkG JMJ Qbe (B" 67" (3cjejGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B50 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WHjYjGJ (B730) s
Keywords: (3GdcjejGA h GdWHjYjGJs